THE FORMATION OF THE NATIONAL IDENTITY OF STUDENTS IN THE STUDY OF THE COURSE "HISTORY" - Natalia A. Tatarenkova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article discusses the importance of teaching the course "History" in high school for the formation of national identity of modern Russian society. Historical memory is regarded as the basis of national identity. The importance of the development of students' ability to comprehend the social experience of previous generations. It focuses on the conduct of the national-patriotic conception of Russian history, education of respect to the past of the country. It is pointed out that the victory in the Great Patriotic War is a cornerstone of the national civil identity. Reveals the author's teaching experience in the preservation of the historical memory of the younger generation, which can be claimed in practice. It is proposed to build on the "pantheon of heroes" that can unite society and to feel ownership to the history of the country.